Crime Reporting Patterns and Frequencies in Print Media in Postcovid Nigeria: A Security Approach - Tajudeen Yusuf ADEYINKA; Musediq Olufemi LAWAL; Olawale Olufemi AKINRINDE; Remi Kasali ALATIS (Bulletin of "Carol I" National Defense University, 2024)
This study systematically delves into the intricacies of crime reporting by mass media in postcovid Nigeria, shedding light on its profound impact and intensity. Through meticulous archival methods, historical editions of The Guardian and Punch newspapers were analyzed over three years. The findings highlight a notable emphasis on crimes against individuals, such as murder and assault, compared to other categories like financial and drug-related crimes. Over 4,093 crime incidents were reported, with crimes against persons dominating in 2021 and 2022. The study underscores the need for nuanced crime reporting and advocates for substantive engagement through editorials and analyses. By fostering awareness and discourse, print media can play a pivotal role in shaping public understanding of crime dynamics and promoting societal well-being.